La villa del Socorro y el Pacto Social en la revuelta comunera: resistencia ante las reformas borbónicas en el Virreinato de la Nueva Granada - María Angélica Del Mar Mendoza Manotas; Ronaldo Junior Cervantes Mendoza (Eleuthera)
This paper analyzes how the town of Socorro, the epicenter of the 1781 Comunero Revolt, became the key site for Neogranadine resistance against the Bourbon reforms imposed since 1777. Through the study of the social pact between the Creole aristocracy and popular sectors, the rebellion is examined as a collective rejection of the economic measures implemented by the royal envoy Gutiérrez de Piñeres, and how this alliance contributed to the formation of a national identity. The main objective of this paper is to analyze the emergence of the social pact during the Comunero Revolt as a mechanism of resistance against Bourbon reformism, and how this process contributed to the development of a collective identity in Nueva Granada. By analyzing historical phenomena, the paper seeks to understand the social dynamics that shaped the formation of Colombia and explain its contemporary issues. A legal-economic approach is adopted to understand how the legal order was configured in relation to socioeconomic spheres, and how the Comunero Revolt reflected a collective resistance against the Bourbon reforms and contributed to the shaping of Neogranadine national identity.